Principals' and teachers' perceptions on principals' instructional management behaviors in aboriginal schools / Agalita anak Joseph - Joseph, Agalita (2014)
This study explores the principals' and teachers' perceptions on principal's instructional management behaviors in managing the school. The difference between the teachers' and principal's views was analyzed to identify differences between their views. The study also explores how the personal variables of teachers influence teachers' perceptions on their principal's instructional management behaviors. There were 38 respondents taken out as samples using a random sampling method from the population. The population of this study is the principals and teachers who are teaching in the aboriginal schools in Selangor. The need to study the principal's instructional management behaviors is critical to the notion that developing a successful learning environment for all students, especially in the aborigine-based schools is depending on collegial environment among teachers and principals. This study is involved both quantitative and qualitative approach for data analysis and the instruments used were the Hallinger (1984) Principal Instructional Management Rating Scale (PIMRS) and interview. Descriptive analysis and one-way ANOVA analysis were used to analyze the mean and frequency and the correlation between the variables in this study. The study indicates that teachers seen the school principal as being able to frame and communicate the school goals and mission effectively to the members of the school community by discussing them at the faculty meetings (M = 3.23, SD = .545). On the other hand, the principals were very concerned in engaging a bonding with the indigenous students by providing incentives for learning (M = 3.90, SD = .141). The study also shows that there have significant differences between the gender, academic qualification and seniority in certain elements of instructional management behaviors. Additionally, this study also revealed the perceptions and challenges faced by the principals and teachers in practicing the instructional management behaviors. The findings of this study may bring changes to the indigenous community education level especially when instructional management is revised and improved. This study is limited only to the principal instructional management behaviors and hence further studies are suggested on other forms of factors that influence the instructional practices in the aboriginal schools.